ANÁLISIS TELEVISIVOS Y SU IMPACTO EN EL APRENDIZAJE DE LOS NIÑOS DEL SECTOR GRITO DE LA LIBERTAD PARROQUÍA VENÚS DEL RÍO QUEVEDO AÑO 2022. - Orejuela Cedeño, Hillary Nathalia (2023)
Television is considered as a means of communication, and part of family entertainment is one of the media preferred by people for its excellence in showing programming content with moving images, sound, of excellent quality at the choice of the consumer. Today the incorporation of new technology with internet, satellite connection, Ultra 4k 3d TV designs have made the figures increase and that its acquisition every year has a greater demand as part of the home. The objective of this research is to carry out an analysis of television programming and the impact it generates on learning in adolescents in the Griot de la Libertad sector, Venus del Rio Quevedo parish, determining that the little control of parents in children over the programming they watch has influenced many of them. infants spend long hours watching television programming, problems of low academic performance, have not done their homework, are not interested in developing their learning, have problems with reading, writing, math operations, there are concentration problems, drowsiness, are easily distracted, generating negative results of low qualifications. For the development of the study, we proceeded to apply the use of research methods and techniques that were used precisely to obtain information, concluding that minors who neglect their academic tasks lose communication with their families, negatively influencing their integral development due to that some of the programs that are transmitted lack elementary values for the formation of young people.